Fusarium Wilt: A New Threat to Florida Lettuce Production - German Sandoya; Jesse J. Murray; Richard N. Raid; Christian F. Miller (EDIS)
Fusarium wilt of lettuce is a disease caused by the fungus Fusarium oxysporum f.sp. lactucae. The disease is present in all lettuce production areas worldwide. Recently this disease has been identified in Florida in localized fields. This new 4-page publication of the UF/IFAS Horticultural Sciences Department presents information about the disease, symptoms, and control measures useful to lettuce growers in Florida. Following these recommendations may help to avoid the spread of this fungus in muck soils at the Everglades Agricultural Area (EAA), where 90% of the lettuce in Florida is planted. Written by Germán V. Sandoya, Jesse J. Murray, Richard N. Raid, and Christian F. Miller. https://edis.ifas.ufl.edu/hs1385